Fire ant-venom anaphylaxis prevalence in the general population and patients with systemic mastocytosis - McMurray, Jeremy C.; Schornack, Brandon J.; Adams, Karla E.; McCoy, Robert L.; Marshall, Amanda K.; Brunader, Janet A.; Maric, Irina; Metcalfe, Dean D.; Boggs, Nathan A. (Frontiers in Allergy, 2025)
BackgroundStinging Hymenoptera can induce fatal anaphylaxis, especially in patients with systemic mastocytosis. Fire ants, Solenopsis invicta and S. richteri, from South America have recently colonized three continents. Prevalence of fire ant-venom anaphylaxis in the general population and in systemic mastocytosis is unknown. The aim was to determine fire ant-venom anaphylaxis prevalence among Tricare beneficiaries and those with systemic mastocytosis.MethodsWe queried the beneficiary immunotherapy prescription database for patients who received immunotherapy with Hymenoptera venom or fire ant whole-body extract and the Tricare beneficiary population health registry database for patients with an ICD−10 code for Hymenoptera venom allergy (HVA). Greater than 95% of the beneficiary population were patients living in the United States. Chart review of a random sample of 150 patients linked to a HVA ICD-10 code was performed to determine the percent of patients with Hymenoptera-venom anaphylaxis. Retrospective review of a systemic mastocytosis cohort was performed to assess fire ant-venom anaphylaxis rate and treatment patterns.ResultsFire ant immunotherapy was the most frequently ordered individual immunotherapy prescription 45.9% (n = 878). Fire ant prescriptions surpassed all flying Hymenoptera immunotherapy prescriptions combined in six states. Fire ant and flying Hymenoptera-venom anaphylaxis prevalence in the general population was 0.048% and 0.083%, respectively. Fire ant-venom anaphylaxis prevalence in the 14 colonized states was 0.085%. More patients with systemic mastocytosis had anaphylaxis triggered by fire ant than all flying Hymenoptera combined.ConclusionFire ant-venom anaphylaxis prevalence in the general population and patients with systemic mastocytosis is higher than all flying Hymenoptera-venom anaphylaxis combined in colonized states. Fire ant-venom anaphylaxis in systemic mastocytosis is frequently misdiagnosed and not treated with epinephrine.